Bioelectrical impedance vector analysis and clinical outcomes in patients with acute heart failure. Issue 4 (April 2016) - Núñez, Julio; Mascarell, Beatriz; Stubbe, Hans; Ventura, Silvia; Bonanad, Clara; Bodí, Vicent; Núñez, Eduardo; Miñana, Gema; Fácila, Lorenzo; Bayés-Genis, Antonio; Chorro, Francisco J.; Sanchis, Juan
Abstract : Supplemental Digital Content is available in the text Abstract : Aims: Fluid overload is a hallmark in acute heart failure (AHF). Bioelectrical impedance vector analysis (BIVA) has emerged as a noninvasive method for quantifying patients' hydration. We aimed to evaluate the effect of BIVA hydration status (BHS) measured before discharge on mortality and rehospitalization for AHF. Methods: We included 369 consecutive patients discharged from the cardiology department from a third-level hospital with a diagnosis of AHF. On the basis of BHS, patients were grouped into three categories: hyper-hydration (>74.3%), normo-hydration (72.7–74.3%) and dehydration (<72.7%). Appropriate survival techniques were used to evaluate the association between BHS and the risk of death and readmission for AHF. Results: At a median follow-up of 12 months (interquartile range, IQR: 5–19), 80 (21.7%) deaths and 93 (25.2%) readmissions for AHF were registered. The mortality and readmission rates for the BHS categories were hyper-hydration (3.28 and 3.83 per 10 persons-years); normo-hydration (1.43 and 2.68 per 10 persons-years); and dehydration (2.24 and 2.53 per 10 persons-years) ( P  < 0.05 for all comparisons). In an adjusted analysis, BHS displayed a significant association with mortality ( P  = 0.004), with a higher mortality risk in those with hyperhydration. Likewise, BHS showed to linearly predict AHF-readmission risk [hazard ratio 1.06 (1.03–1.10); P  = 0.001 per increase in 1%]. Conclusion: In patients admitted with AHF, BHS assessed before discharge was independently associated with the risk of death and AHF-readmission.